Effect of a chair and computer screen height adjustment on the neck and upper back musculoskeletal symptoms in an office worker - Saggu, Rajinder Kaur (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScPhysio)--Stellenbosch University, 2015.